Investigationn and Evaluation of Cross-Border Truck Transportation from Mae Sot-Myawaddy to Yangon - Kesinee Saowadee; Suthep Nimsai; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2015)
This study investigates both direct and indirect factors that effected to cross-border truck transportation from Mae Sot-Myawady to Yangon. The scope of study was adopted on the theory of Kent (1989) and Ballou (1992) ,which focusing on cost, time, reliability. Cooperative participated with 200 of respondents for collecting data employed the SEM model and used Confirmatory Factor Analysis (CFA) for finding factor loading. The study was found that the reliability of transportation provider was the most important factor which effected to cross-border truck transportation with factor loading equal 0.92. Even though, trader and transport participants who used Mae Sot-Myawaddy to Yangon route should also concern other related factors due to instability and minority conflicts in Myanmar. This study could be a potential advantageous guideline for forming competitive advantages and strategy development of using cross-border truck transportation.